SIFAT FISIK DAN MEKANIK KAYU BENUANG (Octomeles sumatrana Miq) YANG DIDENSIFIKASI BERDASARKAN SUHU DAN WAKTU KEMPA - rino, Sa; H. Usman, Fadillah; haida, Nur (Universitas Tanjungpura, 2013)
Benuang (Octomeles sumatrana Miq) wood less attractive to industrial carpentry, because of Benuang wood has a low at strength level (strength class IV - V). Densification of wood is one solution, which is the timber compaction process that aims to improve the strength and durability of the wood. There are two factors for treatment in this study that include temperature factors felts (1700C, 1800C and 1900C) and Time Felts (50 minutes and 60 minutes). Samples made ??of from Benuang with wood measuring 30 cm (L) x 8 cm (W) x 4 cm (H), then steamed in an autoclave and hot pressed (hot press) with a target thickness of 30% and the pressure felt by 60 kg/cm2. Then created a test sample for testing. The parameters measured are physical properties (color and touch wood impression, moisture content, density and dimensional changes) and mechanical properties (static bending persistence / Modulus of Elasticity, strength of bending fracture / Modulus of Rupture, and firmness press parallel fiber / Cruishing Maximum Strength). The design that used in this study is a 3x2 factorial experimental design in a completely randomized design (CRD) with 3 replications. Results showed that the densification process on wood Benuang generally not been able to increase the strength of the timber, that is still in the same class with the timber control (strenght class IV-V). But partially strength there is still best value that on the showed densification timber with temperature 1800C with clamp time for 60 minutes, with decrease in water content of 43.12%, increase in value density of 27,22%, dimensional change impairment of 7,57%, MOE impairment of 71,61%, MOR values ??decrease by 61,93% and MCS impairment of 18,41%. Keyword : Octomeles sumatrana